Identification of enhancers responsible for the coordinated expression of myosin heavy chain isoforms in skeletal muscle - Keren Long; Duo Su; Xiaokai Li; Hengkuan Li; Sha Zeng; Yu Zhang; Zhining Zhong; Yu Lin; Xuemin Li; Lu Lu; Long Jin; Jideng Ma; et al. (BMC Genomics, 2022)
Abstract Background Skeletal muscles consist of fibers of differing contractility and metabolic properties, which are primarily determined by the content of myosin heavy chain (MYH) isoforms (MYH7, MYH2, MYH1, and MYH4). The regulation of Myh genes transcription depends on three-dimensional chromatin conformation interaction, but the mechanistic details remain to be determined. Results In this study, we characterized the interaction profiles of Myh genes using 4C-seq (circular chromosome conformation capture coupled to high-throughput sequencing). The interaction profile of Myh genes changed between fast quadriceps and slow soleus muscles. Combining chromatin immunoprecipitation-sequencing (ChIP-seq) and transposase accessible chromatin with high-throughput sequencing (ATAC-seq), we found that a 38 kb intergenic region interacting simultaneously with fast Myh genes promoters controlled the coordinated expression of fast Myh genes. We also identified four active enhancers of Myh7, and revealed that binding of MYOG and MYOD increased the activity of Myh7 enhancers. Conclusions This study provides new insight into the chromatin interactions that regulate Myh genes expression.